2004
DOI: 10.1063/1.1645519
|View full text |Cite
|
Sign up to set email alerts
|

Confinement of plasmas of arbitrary neutrality in a stellarator

Abstract: The equilibrium, stability, and transport of pure electron plasmas confined on magnetic surfaces is reviewed. The prospects for creation of partly neutralized plasmas and electron–positron plasmas confined in a stellarator are discussed. The Columbia Non-neutral Torus, a small ultrahigh vacuum stellarator being constructed at Columbia University, is being built to systematically study non-neutral plasmas confined on magnetic surfaces. The experimental design is discussed in the context of relevant physics para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Furthermore, it has been suggested that the creation of electron-positron plasma in pulsars is essentially by energetic collisions between particles which are accelerated as a result of electric and magnetic fields in such systems (Sturrock 1971;Michel 1982Michel , 1991. On the other hand, the successful achievements for creation of the electron-positron plasmas in laboratories have been frequently reported in the scientific literatures (Gibson et al 1960;Gahn et al 2000;Pedersen et al 2003;Helander & Ward 2003;Amoretti et al 2003;Pedersen et al 2004;Chen et al 2009). In this regard, many authors have concentrated on the relativistic electron-positron plasmas (Berezhiani et al 1993;Verheest 1996;Gedalin et al 1998;Keston et al 2003;Muoz 2004;Laing & Diver 2006) because of its occurrence in astrophysics and encountering with positron as an antimatter in high-energy physics.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been suggested that the creation of electron-positron plasma in pulsars is essentially by energetic collisions between particles which are accelerated as a result of electric and magnetic fields in such systems (Sturrock 1971;Michel 1982Michel , 1991. On the other hand, the successful achievements for creation of the electron-positron plasmas in laboratories have been frequently reported in the scientific literatures (Gibson et al 1960;Gahn et al 2000;Pedersen et al 2003;Helander & Ward 2003;Amoretti et al 2003;Pedersen et al 2004;Chen et al 2009). In this regard, many authors have concentrated on the relativistic electron-positron plasmas (Berezhiani et al 1993;Verheest 1996;Gedalin et al 1998;Keston et al 2003;Muoz 2004;Laing & Diver 2006) because of its occurrence in astrophysics and encountering with positron as an antimatter in high-energy physics.…”
Section: Introductionmentioning
confidence: 99%
“…1 While Penning traps are limited to the confinement of like-charged particles, a magnetic surface configuration such as that of a stellarator can confine plasmas of arbitrary neutrality. 2 This type of device is capable of exploring a wide range of new physical phenomena with relevance to basic plasma physics, particle physics, and fusion science. By introducing positrons into an electron plasma confined on magnetic surfaces, a plasma can be formed in which positrons are confined not only by the magnetic surfaces, but also by the potential well created by the electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Pure toroidal traps [5,6] have been successfully used to confine nonneutral plasmas, and have also been used to study quasi-neutral plasmas [7], but have to date not yet confined and sustained partially neutralized plasmas. Stellarators, exhibiting closed particle orbits at any degree of neutralization, are predicted to be able to confine plasmas of arbitrary neutrality [8,9].…”
Section: Introductionmentioning
confidence: 99%